An analysis on the factors affecting entrepreneurial intentions of white-collar employees - Sivri, Nihan (My University, 2020)
Girişimcilik niyeti literatürde açıklanan en temel anlamı ile bireyin kendi işine sahip olma arzusunu ifade eder. Girişimcilik niyeti kavramsal olarak açıklayan en önemli çalışmalar; Shapero ve Sokol Girişimci Olay Modeli, Bird Girişimci Niyet Modeli ve Ajzen Planlı Davranış Teorisi’dir. Bir değişken olarak girişimcilik, ergenlik dönemindeki yaşam boyu deneyimler, girişimci kişilik özellikleri ve girişimcilik yeterliliğinden etkilenir. Girişimci kişilik, değişime açık, dışa dönük, öz disiplinli, duygusal olarak dengeli ve benmerkezci olarak tanımlanabilir.Bu tez çalışmasının temel amacı, beyaz yakalı çalışanların girişimci niyetleri, psikolojik sermaye ve alan tutumları arasındaki ilişkileri incelemektir. Bu anlamda girişimcilik niyetlerini etkileyen önemli faktörlerin belirlenmesi amaçlanmıştır.

Entrepreneurial intention refers to the desire of the individual to have their own business in the literature. The most important studies that conceptually explain the entrepreneurial intention are Shapero and Sokol' entrepreneurial event model, Bird's entrepreneurial intention model and Ajzen's planned behavior theory. Entrepreneurship as a variable is affected by lifelong experiences, entrepreneurial personality traits, and entrepreneurial competence in adolescence. Entrepreneurial personality could be defined as open to change, extroverted, self-disciplined, emotionally balanced and egocentric.The main purpose of this thesis study was to investigate the relationships between entrepreneurial intentions, psychological capital and domain attitudes of white-collar employees. In this sense, it was aimed to identify significant factors that affect their entrepreneurial intentions.
Keywords: Business; girişimcilik niyeti psikolojik sermaye beyaz-yakalı çalışanlar entrepreneurial intention white-collar employees psychological capital psycap domain attitudes; İşletme; Management; Yönetim